An Investigation of Multidimensional Energy Poverty in Pakistan (The Pakistan Development Review, 2013)
Poverty is an alarming problem all over the world. It is one of the severe challenges today faced by not only the developing nations but by the developed nations also. However, the problem is worst in developing countries [United Nations and IEA (2010)]. All these countries face poverty in different forms such as food poverty, energy poverty, shortage of natural resources, shortage of agricultural products, lack of shelter and clothing among others. It is persuasive to correlate poverty with lack of energy consumption also. Such a correlation identifies that poor use energy very inadequately [Pachauri, et al. (2004)]. Energy helps societies to move from one development stage to another. Worldwide energy demand is increasing while supply is decreasing due to increase in the world population, emerging economies and economic development. In current day to day life energy has become an essential requirement. For all of us energy is required for lighting, transportation, cooking, health services, and to fulfill many of our basic needs. Electricity access at household level enhances telecommunication, entertainment, and knowledge via radio, television, and computer etc.